2000
DOI: 10.1007/s004010000200
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of apolipoprotein E within prion-associated lesions in squirrel monkey brains

Abstract: The interaction of various amyloid precursors and apolipoprotein E (apoE) is important for Congophilic amyloid formation. As for cerebral amyloidoses, although the correlation between amyloid beta protein (Abeta) and apoE in Alzheimer's disease (AD) has been clarified, the interaction of prion protein isoform (PrPsc) and apoE in several types of prion diseases (PDs) has not been examined in detail. ApoE colocalization has been confirmed in Congophilic PrPsc plaques, but to clarify the participation of apoE in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Apolipoprotein E is involved in neural repair and contributes to neuronal survival (Beffert et al, 2006;Gutman et al, 1997;Poirier et al, 1991). Moreover, increased expression of apolipoprotein E and immunohistological co-localization of apolipoprotein E and PrP have been described in animal models of transmissible spongiform encephalopathies (Diedrich et al, 1991;Hochstrasser et al, 1997;Nakamura et al, 2000), suggesting that apolipoprotein E is involved in the pathogenesis of prion diseases. Similarly, enhanced clusterin/apolipoprotein J levels have been found in prion-related encephalopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein E is involved in neural repair and contributes to neuronal survival (Beffert et al, 2006;Gutman et al, 1997;Poirier et al, 1991). Moreover, increased expression of apolipoprotein E and immunohistological co-localization of apolipoprotein E and PrP have been described in animal models of transmissible spongiform encephalopathies (Diedrich et al, 1991;Hochstrasser et al, 1997;Nakamura et al, 2000), suggesting that apolipoprotein E is involved in the pathogenesis of prion diseases. Similarly, enhanced clusterin/apolipoprotein J levels have been found in prion-related encephalopathies.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE transports cholesterol in plasma and in the brain, a critical function known to be perturbed in many neurodegenerative disorders including Alzheimer's disease 53. ApoE is also known to bind various amyloidogenic proteins 54 and has been shown to co‐localize with PrP Sc deposits in vivo 28, 55. Thus, its presence in PrP Sc preparations from prion‐infected brains may simply be due to its ability to bind PrP Sc .…”
Section: Discussionmentioning
confidence: 99%
“…ApoE is also known to bind various amyloidogenic proteins [54] and has been shown to co-localize with PrP Sc deposits in vivo [28,55]. Thus, its presence in PrP Sc preparations from prion-infected brains may simply be due to its ability to bind PrP Sc .…”
Section: Discussionmentioning
confidence: 99%
“…In prion diseases apoE binds to prion amyloid plaques and its phenotype plays an important role in the amyloid genesis process and acceleration of the PrP aggregation [14,18]. It has been suggested that ApoE4, when combined with valine at codon 129, may increase the total amount of prion protein deposited in plaque form.…”
Section: Discussionmentioning
confidence: 99%